Dental emergencies presenting to a university-based paediatric dentistry clinic in the West Indies - R. S. NAIDU, D. BOODOO, T. PERCIVAL, & J. T. NEWTON (Paediatric Dentistry, 2005)
Adequate provision of primary dental care must include emergency care for children. These services are often delivered within dental teaching hospitals, and together with offering a service to the public, provide clinical exposure and training for dental undergraduate and postgraduate students.